The geography of genetic data: Current status and future perspectives - Peng, Xin; Li, Qiang; Cheng, Zhentao; Huang, Xiaolei (Frontiers in Ecology and Evolution, 2023)
The biogeography field benefits more and more from the growth and application of genetic data such as nucleotide sequences and whole genomes. It has been perceived by scientists that genetic data may be imbalanced among different geographical regions and taxonomic groups. However, the lack of empirical evidence prevents the understanding of current data volume and distribution of genetic data. Based on the construction of a dataset including records for 365 millions of nucleotide sequences of Animalia, Plantae and Fungi kingdoms, 6 millions of COI sequences of insects, 77 thousands of COI sequences of mammals, 220 thousands of rbcl sequences of Magnoliopsida, and 44 thousands of ITS sequences of Dothideomycetes, here we present evidence on geographical and taxonomical imbalance of the genetic data, identify major gaps and inappropriate practices in the production, application and sharing of genetic data. We then discuss our perspectives on how to fill up gaps and improve the quantity and quality of genetic data.